2018
DOI: 10.3892/mmr.2018.8582
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bioactive heterocyclic compounds from mulberry and their protective effect against streptozotocin-induced apoptosis in INS-1 cells

Abstract: A phytochemical investigation of the MeOH extracts from mulberries (the fruit of Morus alba L.) led to the identification of six heterocyclic compounds (1‑6). These compounds were screened to detect whether they protected pancreatic INS‑1 cells from streptozotocin (STZ)‑induced cytotoxicity. Compound 3 was the most effective at preventing STZ‑induced cytotoxicity and the production of reactive oxygen species (ROS) in INS‑1 cells. In addition, compound 3 effectively prevented apoptosis induced by STZ in INS‑1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…These findings are inconsistent with previous findings on STZ treated INS-1 cells. On the other hand, treating the INS-1 cells with 2.5 and 5 µM of CA acid reversed the STZ effect and protected against apoptosis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are inconsistent with previous findings on STZ treated INS-1 cells. On the other hand, treating the INS-1 cells with 2.5 and 5 µM of CA acid reversed the STZ effect and protected against apoptosis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…((R)-5-hydroxypyrrolidin-2-one, methyl(R)-pyroglutamate, loliolide, 3-benzofuran carboxaldehyde and odisolane, which protected pancreatic INS-1 cells from streptozotocin-induced cytotoxicity. 25 2.1 | Five and six-membered ring synthetic heterocycles…”
Section: Five-membered Ring Natural Heterocyclicsmentioning
confidence: 99%
“…We also identified butyl pyroglutamate from M. alba fruits as a nephroprotective agent against cisplatin-induced kidney cell death in LLC-PK1, and its effect was found to be mediated by attenuation of the phosphorylation of c-Jun N-terminal kinase, MAPK, ERK, p38, and caspase-3 [41]. In particular, we recently found that loliolide, a heterocyclic compound in M. alba fruits, showed a protective effect against streptozotocin-induced apoptosis of INS-1 cells via inhibition of the caspase signaling pathway and induction of B-cell lymphoma-2 (Bcl-2) protein expression, suggesting that the active compound could be effective in preventing diabetes mellitus [42]. In the present study, the ethanol extract of M. alba fruits was further investigated to identify potential antidiabetic natural compounds, as there have been few studies on the antidiabetic compounds identified from M. alba and their underlying mechanisms of action, although it has been used in traditional medicine to lower blood sugar levels [36], and M. alba extracts are known to exhibit antidiabetic properties [37,38].…”
Section: Introductionmentioning
confidence: 99%